Using video-recording as a tool for learners' self-reflection in oral presentation: Teachers' perceptions and practices - Nguyen, Tran Nam Phuong (Cantho University, 2014)
By conducting the study, the researcher would like to seek the answer to the following questions: what are the perceptions of EFL teachers toward using video-recording as a tool for learners' self-reflection in oral presentation"? What are EFL teachers' classroom practices of using video-recording as a tool for learners' self-reflection in oral presentation? Is there any mismatch between EFL teachers' perceptions and practices and what are its underlying reason, if any?